Pelaksanaan Fungsi Koordinasi Antara Pemerintah Daerah Dan Pt. Energi Bayu Dalam Pembangunan Pembangkit Listrik Tenaga Bayu (PLTB) Kabupaten Jenepoto - Alifiah, Firdha; Muhammadiah, Muhammadiah; Setiawati, Budi (Universitas Muhammadiyah Makassar, 2020)
This study purposed to determine the implementation of the coordination function in prevention between the Regional Government and PT. Bayu Energy Development of Bayu Power Plant (PLTB) in Jeneponto Regency. This study was a qualitative descriptive study, while data collection techniques used observation, interviews and documentation. While the informants in this study were 8 people. Data sources used were primary data and secondary data, data analysis techniques with data reduction, data presentation and verification. The results showed that the Implementation of the Coordination Function between the PUPR Office and PT. Bayu Energy in PLTB Development in Jeneponto Regency had not run optimally, seen from the aspect of conflict prevention and contradiction, it did not find any solutions in its settlement, because the coordination requested by the PUPR Office was not responded by PT. EBJ, aspects of prevention of wastefulness prevention of wastefulness that occured between the two parties each opinions on the SOP that governed it, the aspect of preventing differences in approach did not work optimally because it had a different approach, and the prevention of differences in implementation did not run well because there was no division of labor.